Pengaruh Iklim Kerja terhadap Semangat Kerja Guru di MAN 1 Medan - Chairunnisa Sagala; Candra Wijaya; Khairuddin Khairuddin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyse the effect of work climate on teacher morale at MAN 1 Medan. Work climate is an important factor in creating a work atmosphere that supports the performance and motivation of educators. Teachers' morale, as an indicator of the success of the education process, is influenced by various aspects, including interpersonal relationships, leadership of the madrasah head, and work environment conditions. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to 50 teachers at MAN 1 Medan. Work climate variables were measured through dimensions such as leadership, openness of communication, and peer support. Meanwhile, morale was measured through indicators of productivity, motivation, and commitment to duty. Data analysis was conducted using simple linear regression technique to determine the relationship and influence between the two variables. The results showed that work climate has a significant influence on teachers' morale at MAN 1 Medan. This finding indicates that a positive work climate, characterised by open communication, adequate support, and inspirational leadership, can significantly improve teachers' morale. Conversely, a less conducive work climate negatively impacts teachers' motivation and performance. This study concludes that effective work climate management is an important strategy in improving teachers' morale. The madrasah is advised to pay attention to the aspects that make up the work climate, such as rewarding performance, creating a harmonious working atmosphere, and ensuring good communication between the madrasah head and teachers. Thus, the quality of education at MAN 1 Medan can continue to be improved through strengthening the morale of the teaching staff.